The effects of polarized training on time trial performance in trained and highly-trained triathletes - Rivera Kofler, T.; Cortés-Roco, G.; Garcia-Carrillo, E.; Olivares-Arancibia, J.; Yáñez-Sepúlveda, R. (Journal of Human Sport & Exercise, 2025)
The polarized training model (POL), with its unique training intensity distribution (TID), emerges as an effective alternative to improve time trial performance. This study aimed to evaluate the effects of 13 weeks of training by applying a POL model in trained and highly-trained triathletes, using a percentage of TID of 75/0/25 in zones 1, 2, and 3, respectively. To analyse training effects, the assessment was performed at the beginning and the end of the study on time trials: 200m swimming (T200m), 4 minutes (T4min) and 20 minutes (T20min) cycling, and 6 minutes (T6min) running. Analysis of covariance (ANCOVA), supplemented with post hoc tests, revealed that POL training did not produce significant changes: T200m (pre = 3.03 ± 0.58, post = 2.90 ± 0.53, p = .59), T4min (pre = 272.09 ± 55.91, post = 290 ± 69.33, p = .50), T20min (pre = 204.91 ± 51.3, post = 216.36 ± 56.6, p = .62) and T6min (pre = 15.71 ± 1.69, post = 15.86 ± 1.54, p = .82). Even though training time in Z1 and Z3 is relevant, our results suggest that optimal programs for trained and highly trained triathletes should not exclude training in Z2. Furthermore, to optimize the effects of the POL model, it is essential to consider the athlete`s initial level of performance and the duration of the program.